A photovoltaic array simulator based on current feedback fuzzy PID control - Shao, Wu; Meng, Zhi-Qiang; Zhou, Hua-An; Zhang, Kai (Journal of intelligent & fuzzy systems, 2015)
A photovoltaic array simulator is designed based on a Buck DC converter with a fuzzy PID control algorithm to account for current feedback. The conventional PID controller cannot self-tune the parameters, therefore the new algorithm uses a fuzzy controller to solve the problem. The difference between the reference current and the real-time feedback current of the Buck converter and its rate of change are regarded as two input variables of the fuzzy controller. The fuzzy controller outputs the adjustment quantities, which are then used to adjust the PID parameters. Next, the duty cycle of the electronic power switch is adjusted by a closed-loop fuzzy PID algorithm to make the output current of the simulator work at the anticipated point of the photovoltaic array on the I-V characteristic curve and realize the simulation of photovoltaic characteristics. Results of the simulation and experiment indicate that the proposed fuzzy PID control simulator can not only accurately simulate the static output characteristics of a photovoltaic cell, but can also rapidly realize the dynamic characteristics when the load or the external environment changes. The approximate error was less than 3.6% , the overshoot was less than 3.5% , the ripple coefficient was less than 3% , and the tracking time was approximately 0.3s. The fuzzy PID control simulator can work well as PV array experiment equipment for the research and development of photovoltaic systems.